The chosen - Matharu, Taran (Matharu, Taran. Contender, 2019)
Cade is settling into a new boarding school, contemplating his future, when he finds himself transported to another realm. He soon discovers their new world is populated with lost remnants from the past: prehistoric creatures, ancient relics, and -- stranger still -- people. Overwhelmed by his new surroundings, Cade has little time to adjust, for soon he and his fellow classmates are forced to become contenders in a brutal game, controlled by mysterious overlords. But, who are these beings and why did they choose these teens? Cade must prepare for battle ... because hiding is not an option.